Chinese language teachers' expectations and perceptions of American students' behavior: Exploring the nexus of cultural differences and classroom management. (April 2015) - Zhou, Wenying; Li, Guofang
Abstract: This paper reports on six Chinese language teachers' experiences and perceptions of their classroom management in the United States of America. The analysis revealed that the teachers experienced cultural mismatches between their Chinese cultural expectations and American students' actual classroom behavior and struggled with challenges of understanding the demands of American classroom management, lack of effective strategies for managing American classroom, and language barriers. However, the teachers were able to adopt strategies commonly used by American teachers to manage their American students while retaining some of their Chinese practices. The findings suggest that cultural differences in classroom management play a significant role in affecting Chinese language teachers' classroom instruction and must be addressed in Chinese language teachers' preparation programs as well as their continued professional development in the U.S. and similar contexts.